An Interdisciplinary Study on the Environmental Reflection of Prehistoric Mining Activities at the Mitterberg Main Lode (Salzburg, Austria). (3rd March 2013) - Breitenlechner, E.; Stöllner, TH.; Thomas, P.; Lutz, J.; Oeggl, K.
<x xml:space="preserve">Abstract</x> A multi‐proxy study by palynological, geochemical, archaeological and dendrochronological analyses discloses the mining activities at the Mitterberg Main Lode. By these means, several mining phases with varying intensity are recorded during the Bronze and Early Iron Age, whereupon a west to east shift of the mining activity at the Mitterberg Main Lode can be observed. The initial mining phase (Phase II), from the 21st to the 15th centuries bc, is characterized by an opening up of the forest vegetation and, additionally, by slightly elevated heavy metal deposition. Phase III shows a first bloom phase of the chalcopyrite mining during the 14th and 13th centuries bc. Pollen analyses disclose extensive clearings used for pasture and settlement. The increased human impact and higher heavy metal pollution suggest intensive mining activity, which is corroborated by the dendrochronological and archaeological data. Phase IV is characterized by mining activities in progress during the 12th century bc. The pollen data reflect a stabilization of the vegetation and slightly elevated As/Cu/Sb to Sc ratios. During Phase V, in the 11th century bc, new clearings indicate a re‐intensification of the mining activities at the Mitterberg Main Lode. Phase VI, from the ninth century bc onwards, describes a human impact with lower intensity at the mining site. This interdisciplinary study at the Mitterberg Main Lode contributes new environmental data for an important area of past metal mining and extends our understanding of the relationship between miners and their landscape.